Insulin requires A2B adenosine receptors to modulate the L-arginine/nitric oxide signalling in the human fetoplacental vascular endothelium from late-onset preeclampsia - Salsoso, Rocío; Mate, Alfonso; Toledo, Fernando; Vázquez, Carmen M.; Sobrevia, Luis [UNESP] (Elsevier, 2021)
Late-onset preeclampsia (LOPE) associates with reduced umbilical vein reactivity and endothelial nitric oxide synthase (eNOS) activity but increased human cationic amino acid (hCAT-1)–mediated L-arginine transport involving A2A adenosine receptor in the fetoplacental unit. This study addresses the A2B adenosine receptor (A2BAR)-mediated response to insulin in the fetoplacental vasculature from LOPE. Umbilical veins and HUVECs were obtained from women with normal (n = 37) or LOPE (n = 35) pregnancies. Umbilical vein rings reactivity to insulin was assayed in the absence or presence of adenosine and MRS-1754 (A2BAR antagonist) in a wire myograph. HUVECs were exposed to insulin, MRS-1754, BAY60–6583 (A2BAR agonist), NECA (general adenosine receptors agonist) or NG-nitro-L-arginine methyl ester (NOS inhibitor). A2BAR, hCAT-1, total and phosphorylated eNOS, Akt and p44/42mapk protein abundance were determined by Western blotting. Insulin receptors A (IR-A) and B (IR-B), eNOS and hCAT-1 mRNA were determined by qPCR. Firefly/Renilla luciferase assay was used to determine −1606 bp SLC7A1 (hCAT-1) promoter activity. L-Citrulline content was measured by HPLC, L-[3H]citrulline formation from L-[3H]arginine by the Citrulline assay, and intracellular cGMP by radioimmunoassay. LOPE-reduced dilation of vein rings to insulin was restored by MRS-1754. HUVECs from LOPE showed higher A2BAR, hCAT-1, and IR-A expression, Akt and p44/42mapk activation, and lower NOS activity. MRS-1754 reversed the LOPE effect on A2BAR, hCAT-1, Akt, and eNOS inhibitory phosphorylation. Insulin reversed the LOPE effect on A2BAR, IR-A and eNOS, but increased hCAT-1–mediated transport. Thus, LOPE alters endothelial function, causing an imbalance in the L-arginine/NO signalling pathway to reduce the umbilical vein dilation to insulin requiring A2BAR activation in HUVECs.
Keywords: Adenosine; Arginine; Endothelium; Insulin; Nitric oxide; Preeclampsia